PRAISING THE SOUNDS - LUIGI NONO “OMAGGIO A GYÖRGY KURTÁG” - CONSTANTIN, Fulvia Anca (Studia Universitatis Babes-Bolyai Musica, 2025)
Luigi Nono’s cultural creative ideas are recognized in the modern history of music. His works and thoughts on art and sound, his composing implies vision, a connection between science (electronic technology and spatial environment) and art (sound and performance). One of his latest works from 1983, reviewed in 1986, Omaggio a György Kurtág was composed in a period when Nono got a different, unique approach to composition regarding not only the attitude towards performance but also due to his continuous acoustic research.